INOVASI NILAI DALAM KERANGKA PERGERSERAN SAMUDERA BIRU (BLUE OCEAN SHIFT) PADA INDUSTRI KACA LEMBARAN DI INDONESIA - Rudy Subagio (Universitas Airlangga, 2020)
ABSTRACTCompetition in the flat glass market in Indonesia since 2015 has been increasingly severe because much-imported glass has entered Indonesia. The rapid rate of imported glass entering Indonesia is caused by the enactment of the free trade pact in southeast Asia and secondly because of the expansion of the Chinese glass industry that built new factories in the Southeast Asia region, especially in Malaysia. Most of the imported glass entering Indonesia is commodity glass with a lower price compared to local products, while the local industry has difficulties in competing for the price because the production cost is already high. This research aims to explore the basic concepts of strategies carried out by local flat glass companies in the domestic market competition based on the value innovation concept in the framework of “Blue Ocean Shift”. The method is an exploratory case study draws on an in-depth field study conducted in a local flat glass company based in Indonesia. The results show that the Blue Ocean Strategy is more appropriate to be used in the face of competition in the flat glass market compared to the Porter generic strategy used by PT Alpha Glass today. Thus, this research is expected to provide insight into the implementation of the Blue Ocean Strategy in the glass industry comprehensively to assist Alpha Glass in determining future strategic directions.Keywords: Value Innovation, Flat Glass Industry, Blue Ocean Shift ABSTRAKPersaingan di pasar kaca lembaran di Indonesia sejak tahun 2015 semakin berat dengan masuknya kaca impor dari luar. Pesatnya laju impor kaca yang masuk ke Indonesia disebabkan oleh setidaknya dua faktor, pertama karena diberlakukannya pakta perdagangan bebas di Asia Tenggara dan kedua karena ekspansi pabrik kaca China yang membangun pabrik-pabrik baru di wilayah Asia Tenggara, khususnya di Malaysia. Sebagian besar kaca impor yang masuk ke Indonesia adalah kaca komoditas dengan harga lebih rendah dibandingkan dengan produk lokal, sementara industri kaca lembaran lokal mengalami kesulitan untuk menurunkan harga karena struktur biaya produksi sudah terlanjur tinggi. Penelitian ini bertujuan untuk mengeksplorasi konsep dasar strategi yang dilakukan oleh perusahaan kaca lembaran lokal dalam menghadapi persaingan di pasar kaca lembaran berdasarkan konsep inovasi nilai dalam kerangka